Sodium thiosulfate treatment rescues hyperglycaemia-induced pronephros damage in zebrafish by upregulating nitric oxide signalling - Ott, Hannes; Bennewitz, Katrin; Zhang, Xin; Prianichnikova, Mariia; Sticht, Carsten; Poschet, Gernot; Kroll, Jens (The journal of physiology, 2024)
Sodium thiosulfate (STS) is gaining increasing attention in research for its potential therapeutic applications across a spectrum of disease processes beyond its current uses. However, the precise mechanisms of action remain incompletely understood. We investigated the efficacy of STS in treating hyperglycaemia-induced pronephros damage in zebrafish to gain further insight into the underlying mechanisms. Hyperglycaemia was induced in zebrafish by suppressing the pdx1 transcription factor, which plays a crucial role in maintaining physiological pancreatic function. STS was administered by introducing it into the medium of zebrafish larvae. The pronephros structure was analysed at 48 h post-fertilization. Metabolomic profiling and RNA sequencing were conducted on groups exposed to various experimental conditions. Our findings reveal a downregulation of nitric oxide (NO) signalling in zebrafish with a knocked-down pdx1 gene, both metabolomically and transcriptionally. Notably, treatment with STS led to a compensatory upregulation of the NO signalling, ultimately resulting in the rescue of the pronephros structure. Our study provides compelling evidence that targeting NO metabolism by the administration of STS offers a promising strategy for addressing hyperglycaemia-induced organ damage. These findings underscore the potential of STS as a promising therapeutic agent for diabetic complications and warrant further investigation of its clinical applications. Key points Sodium thiosulfate (STS) is increasingly drawing attention in research for its potential therapeutic applications across a spectrum of disease processes. Here, we demonstrate that STS treatment rescues hyperglycaemia-induced pronephros damage in zebrafish. We identified upregulation of nitric oxide signalling as the major driver behind STS-mediated rescue. Our data suggest that STS offers a promising strategy for addressing hyperglycaemia-induced organ damage, including diabetic nephropathy.